Development of a Gold Nanoparticle-Based Lateral-Flow Immunoassay for Pneumocystis Pneumonia Serological Diagnosis at Point-of-Care - Tomás, Ana Luísa; de Almeida, Miguel P.; Cardoso, Fernando; Pinto, Mafalda; Pereira, Eulália; Franco, Ricardo; Matos, Olga (Frontiers in Microbiology, 2019)
Pneumocystis jirovecii pneumonia (PcP) is a major human immunodeficiency virus (HIV)-related illness, rising among immunocompromised non-HIV patients and in developing countries. Presently, the diagnosis requires respiratory specimens obtained through invasive and costly techniques that are difficult to perform in all patients or implement in all economic settings. Therefore, the development of a faster, cost-effective, non-invasive and field-friendly test to diagnose PcP would be a significant advance. In this study, recombinant synthetic antigens (RSA) of P. jirovecii’s major surface glycoprotein (Msg) and kexin-like serine protease (Kex1) were produced and purified. These RSA were applied as antigenic tools in immunoenzymatic assays for detection of specific anti-P. jirovecii antibodies (IgG and IgM) in sera of patients with (n =48) and without (n=28) PcP. Results showed that only IgM anti-P. jirovecii levels were significantly increased in patients with PcP compared with patients without P. jirovecii infection (p≤0.001 with both RSA). Thus, two strip lateral flow immunoassays (LFIA), based on the detection of specific IgM anti-P. jirovecii antibodies in human sera samples, were developed using the innovative association of P. jirovecii’s RSA with spherical gold nanoparticles (AuNPs). For that, alkanethiol-functionalized spherical AuNPs with ca. ≈40 nm in diameter were synthetized and conjugated with the two RSA (Msg or Kex1) produced. These AuNP-RSA conjugates were characterized by agarose gel electrophoresis (AGE) and optimized to improve their ability to interact specifically with serum IgM anti-P. jirovecii antibodies. Finally, two LFIA prototypes were developed and tested with pools of sera from patients with (positive sample) and without (negative sample) PcP. Both LFIA had the expected performance, namely, the presence of a test and control red colored lines with the positive sample, and only a control red colored line with the negative sample. These results provide valuable insights into the possibility of PcP serodiagnosis at point-of-care. The optimization, validation and implementation of this strip-based approach may help to reduce the high cost of medical diagnosis and subsequent treatment of PcP both in industrialized and low-income regions, helping to manage the disease all around the world.